2019
DOI: 10.1292/jvms.18-0691
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary adenofibroma in a sika deer

Abstract: A solitary firm nodule was found in the lung of a sika deer ( Cervus nippon yesoensis ). Histologically, it was a biphasic lesion composed of epithelial and stromal cell elements and exhibited a leaf-like growth pattern. The epithelial cells were immunohistochemically positive for pancytokeratin, cytokeratin 7, napsin A, and thyroid transcription factor-1, and the stromal cells were positive for vimentin and partially positive for desmin and α-smooth muscle actin. These observations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Currently, the pathogenesis of PAF is unclear ( 5 ). Clinical data has shown that most patients with PAF are middle-aged ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the pathogenesis of PAF is unclear ( 5 ). Clinical data has shown that most patients with PAF are middle-aged ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The neoplastic component of PAF remains controversial. Most scholars considered PAF as a biphasic tumor, composed of neoplastic epithelium and stromal spindle cells (14,(18)(19)(20). Other scholars argued that the glandular component of PAF is entrapped normal respiratory epithelium during tumor growth and only stroma is genuine neoplastic component (1,15).…”
Section: Discussionmentioning
confidence: 99%